2016
DOI: 10.1186/s13287-016-0429-6
|View full text |Cite
|
Sign up to set email alerts
|

Microvesicles secreted from equine amniotic-derived cells and their potential role in reducing inflammation in endometrial cells in an in-vitro model

Abstract: BackgroundIt is known that a paracrine mechanism exists between mesenchymal stem cells and target cells. This process may involve microvesicles (MVs) as an integral component of cell-to-cell communication.MethodsIn this context, this study aims to understand the efficacy of MVs in in-vitro endometrial stressed cells in view of potential healing in in-vivo studies. For this purpose, the presence and type of MVs secreted by amniotic mesenchymal stem cells (AMCs) were investigated and the response of endometrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 59 publications
(62 reference statements)
1
35
0
Order By: Relevance
“…This paper describes, for the first time, the isolation and characterisation of EV derived from equine BM-MSC and demonstrates their ability to alter gene expression in normal chondrocytes in the presence of IL-1and TNF-  With regards to EVs in horses we found only six publications were extracellular vesicles had been isolated from any horse tissues (19)(20)(21)(22)(23). Of these six publications, four derive the EVs from adipose derived stem cells and the others are isolated from amniotic stem cells (19)(20)(21)23,24). With regards to the isolation of EVs, ultracentrifugation, size exclusion chromatography or precipitation however, we identified no publications regarding the isolation of equine bone marrow MSC EVs or their applications as a therapeutic (19)(20)(21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper describes, for the first time, the isolation and characterisation of EV derived from equine BM-MSC and demonstrates their ability to alter gene expression in normal chondrocytes in the presence of IL-1and TNF-  With regards to EVs in horses we found only six publications were extracellular vesicles had been isolated from any horse tissues (19)(20)(21)(22)(23). Of these six publications, four derive the EVs from adipose derived stem cells and the others are isolated from amniotic stem cells (19)(20)(21)23,24). With regards to the isolation of EVs, ultracentrifugation, size exclusion chromatography or precipitation however, we identified no publications regarding the isolation of equine bone marrow MSC EVs or their applications as a therapeutic (19)(20)(21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…Of these six publications, four derive the EVs from adipose derived stem cells and the others are isolated from amniotic stem cells (19)(20)(21)23,24). With regards to the isolation of EVs, ultracentrifugation, size exclusion chromatography or precipitation however, we identified no publications regarding the isolation of equine bone marrow MSC EVs or their applications as a therapeutic (19)(20)(21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular vesicle production and secretion were identified by Pascucci et al [33] in equine adipose tissue MSCs and were shown to be involved in the stimulation of angiogenesis. Another important property (anti-inflammatory activity) of extracellular vesicles produced by equine MSCs has recently been demonstrated in in vitro studies involving models of tenocytes [34] and endometrial cells [35].…”
Section: Swiss-prot Accessionmentioning
confidence: 97%
“…MVs seem to be involved in a dynamic mutual paracrine communication between the embryonic and the maternal environment at the early stage of preimplantation embryo development (Saadeldin et al 2015). Recently, Lange-Consiglio et al (2016) and Perrini et al (2016) identified the presence and type of MVs secreted by equine AM-MSCs; the authors also evaluated, in a preliminary study in vitro, the possible therapeutic implication of MVs in endometrial and tendon pathologies. Despite these studies on equine AM-MSCs, the recognized importance of WJ as an alternative source of MSCs both in equine and human medicine (Iacono et al 2012, Subramanian et al 2015 and despite a lot of data have been reported on these features of equine adult MSCs (Pascucci et al 2010, Maia et al 2013, no studies are present on ultrastructural characteristics and MVs of equine WJ-MSCs.…”
Section: Introductionmentioning
confidence: 99%